The Sound of Jacqueline du Pré: Revisiting her Medical and Musical History (2018)
Jacqueline du Pre was a British cellist, famous for her masterful interpretations and her passionate style of playing. Her outstanding musical career was, unfortunately, cut short by multiple sclerosis. In the present paper, we conduct a historical and medical analysis of her life story, discussing a few aspects regarding her illness and treatment options available at the time of her diagnosis.